The effects of combine treatment of memantine and donepezil on Alzheimer's Disease patients and its relationship with cerebral blood flow in the prefrontal area. (17th January 2014) - Araki, Tomoko; Wake, Rei; Miyaoka, Tsuyoshi; Kawakami, Kazunori; Nagahama, Michiharu; Furuya, Motohide; Limoa, Erlyn; Liaury, Kristian; Hashioka, Sadayuki; Murotani, Kenta; Horiguchi, Jun
<x xml:space="preserve">Abstract</x> Background In this study, we evaluated the effect on cognitive function of memantine, behavioral and psychological symptoms of dementia, and the care burden, in patients with moderate‐to‐severe Alzheimer's disease (AD). Furthermore, with near‐infrared spectroscopy (NIRS), we examined the association between effect of memantine and brain blood flow. Methods We evaluated the effect of memantine administration from baseline on Clinical Global Impression‐Improvement scale, mini mental state examination (MMSE), Clock Drawing Test (CDT), Neuropsychiatric Inventory (NPI), Japanese version of the Zarit Burden Interview (J‐ZBI) and NIRS in two groups, donepezil administration memantine combination group (combination group, n = 19) donepezil administration memantine non‐administration group (control group, n = 18) were assessed at weeks 0, 4, 12, and 24. Results Significant difference was found between the combination group and the control group in the score variation of Clinical Global Impression‐Improvement scale, MMSE, CDT, NPI, and J‐ZBI. In the NIRS measurements, trend oxyhemoglobin reduced suppression was observed in some channels centered on the superior frontal gyrus. A significant correlation was observed in the scores of MMSE, CDT, NPI, and J‐ZBI. In addition, a significant positive correlation was also observed between the number of words in NIRS and scores of MMSE and CDT. Conclusions In this study, by administering memantine in AD patients that inhibit the reduction of cerebral blood flow in the prefrontal area and improve clinical symptoms overall cognitive function, behavioral and psychological symptoms of dementia, thereby reducing the care burden of caregivers was suggested. Copyright © 2014 John Wiley & Sons, Ltd.